Expanding Access to Finance : Good Practices and Policies for Micro, Small, and Medium Enterprises - Malhotra, Mohini; Chen, Yanni; Criscuolo, Alberto; Fan, Qimiao; Hamel, Iva lIieva; Savchenko, Yevgeniya (Washington, DC : World Bank, 2012)
This book on micro, small, and medium enterprise (MSME) finance is intended primarily for government policy makers. It presents a policy framework whereby governments can support increased access by MSME to financial services based on empirical evidence and practices. MSME complain that lack of access to finance constrains their growth and competitiveness. Indeed, financial sector policies often work against the ability of commercial financial institutions to serve MSME, albeit often unintentionally. In many countries, lack of competition in the banking sector limits pressure on banks to reach out to MSME client segments. High risk and high transaction costs-real or perceived-associated with bank lending to MSME likewise constrain access. Often, supervisory and capital adequacy requirements penalize banks for lending to enterprises that lack traditional collateral. Attempts by governments to address these constraints and offset the inequalities in financial sector policy generally have not achieved the desired results. This book lays out a market-based policy framework for governments that focuses on delivery of financial services to MSME on commercial terms. The framework guides governments in focusing scarce resources on developing an inclusive financial sector policy; building sound financial institutions; and investing in a supportive information infrastructure, such as credit bureaus and accounting standards. Examples from around the world illustrate how such a strategy has helped build more inclusive financial systems for all.